ATTITUDE, HOW TO LEARN AND CONTROL THEORY OF STUDENT ACHIEVEMENT - khaidir rahman nasir (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
This study aims to determine the effect of attitude, learning and procurement of theory to the learning outcomes of students in Indonesia. The approach used in this study is quantitative. Data analysis technique used in this research include descriptive statistical analysis and multiple regression analysis. The population of all students of Electrical Engineering Education, Faculty of Engineering, University of Makassar, which totaled 662 respondents person. The findings of this study mentions that attitude, how to learn and pengusaaan theory is closely related to the learning outcomes of students in Makassar. All of these variables is very important apply to students who practice in the Lab campus in Indonesia in order to increase learning outcomes as the development of the 4.0 to the 5.0 era.